Total Quality Management implementation in Greek businesses: Comparative assessment 2009-2013 - Martha Vranaki; Stergios Vranakis; Lazaros Sarigiannidis (International Journal of Production Management and Engineering)
The competition in the Greek manufacturing sector has become very intense and the need for businesses to survive, under these very difficult conditions, forces them to find new ways to increase their profits, but also to attract new customers and to retain old.  A necessary condition for long-term business survival is to maintain a high product quality level. The implementation of Total Quality Management (TQM) approach is a key factor to achieve this goal.The main objective of this research is to identify the current situation as far as the implementation of TQM by Greek manufacturing firms, and finally to compare the results between the current research and the previous research of 2009 (Vranaki et al., 2010). The research model that has been developed incorporates nine factors which are found in literature to influence Total Quality Management. A structured questionnaire has been developed and distributed to executives of 61 companies. Descriptive statistics as well as Structure Equation Modeling (SEM) techniques were used to analyze the data.